Chemical profiles and biological potential of tuber extracts from Cyclamen coum Mill - ŞENKARDEŞ, İSMAİL (ELSEVIER, 2021)
Cyclamen coum Mill. used in traditional medicine has been reported to exhibit interesting biological activities. In this study, the ability of the C. coum tuber extracts to inhibit clinical enzymes, namely, cholinesterases, ty-rosinase, alpha-amylase, and alpha-glucosidase, as well as the antioxidant properties were assessed. High -performance liquid chromatography/electrospray ionization quadrupole-time -of-flight mass spectrometer (HPLC- ESI-Q -TOF-MS) was employed to obtain detailed phytochemical proiles and in silico studies were performed against the key clinical enzymes. HPLC- ESI-Q -TOF -MS results conirmed the presence of saponins cyclacoumin and cy-claminorin, which were previously identiied from C. coum tuber extracts. In addition, other phenolic com-pounds, namely, phloretin C -dihexoside, quercetin 3 -galactoside, and catechin, were also identiied from C. coum tuber extracts. The methanol extract showed interesting inhibition against tyrosinase (6 5. 87 mg kojic acid equivalent/g extract) and alpha-glucosidase (3 4. 41 mg acarbose equivalent / g extract). Low inhibition was observed against cholinesterases and alpha-amylase. The methanol also showed active antioxidant properties (expressed as Trolox equivalent [TE]), namely, radical scavenging and reducing potential (1 5. 17 and 21 .8 6 mg TE / g extract, for 2, 2 '- azino- bis(3-ethylbenzthiazoline -6 -sulfonic acid) and cupric reducing antioxidant capacity assays, re-spectively). In order to highlight the possible bioactive compounds responsible of the biological effect, phloretin C -diglucoside, catechin and quercetin 3 -galactoside were docked via in silico molecular modelling ap-proaches. For tyrosinase, quercetin 3 -galactoside showed better docking and free binding energy which was found to bind very strongly to the enzymatic cavity of tyrosinase (via hydrogen bonds to Glu322, His85, His263, Gly281 and pi-pi stacks to His263 and His259). Findings from this study tend to advocate for further in-vestigations focusing on the isolation of bioactive compounds from the methanol extract of C. coum tuber ex-tracts and assessment of their cytotoxicity and their bioactivity.
Keywords: Cyclamen coum; Molecular docking; Cholinesterases; Amylase; Cyclacoumin; IN-VITRO; ANTIOXIDANTS; PERSPECTIVE; SILICO; PARTS; PLANT